Penggunaan Near Infrared Spectroscopy Pada Penentuan Kandungan Padatan Terlaru.t Buah Mangga Indramayu Secara Tidak Merusak - Diding Suhandy; Rofandi Hartanto; Sulusi Prabawati; Yulianingsih .; Mad Yamin (Jurnal Keteknikan Pertanian, 2008)
Near infrared (NIR) spectroscopy appears as a prominent method for nondestructive fruit quality assessment. In this work, the relationship between the nondestructive NIR spectral measurements and the soluble solids content (SSC) of mango fruit was investigated. A number of 92 mango fruits (Mangifera indica var. Indramayu) were used as samples. The samples were divided into two groups, 46 samples for developing calibration model and 46 samples for performing validation. Using a portable spectrometer, spectra for each sample were acquired in absorbance mode at six different positions. The SSC of mango was measured using the digital refraktometer. The Partial Least Squares (PLS) regression was used to develop a calibration model. The NIR spectroscopy method successfully determined the sse of mango fruits with correlation coefficient between predicted and actual values (r) of 0.91, standard error of prediction (SEP) of 0. 74, and bias of 0.02. Keywords: NIR spectroscopy, soluble solids content, absorbance mode, nondestructive method,mangoDiterima: 18 Maret 2008; Disetujui: 17 Juli 2008